Community Welfare With Youth Entrepreneurship And Employment Support Services In Bantaeng Regency - Irwan Misbach (TASAMUH, 2023)
The purpose of the study was to determine the implementation of the YESS program and to find out the inhibiting and supporting factors of the YESS program in Bantaeng regency. Data collection methods used are observation, interviews, and documentation. The main finding in this study is that the YESS program is a very effective program in changing people's mindsets in the agricultural sector and has been proven to improve community welfare. The results of this study indicate that the YESS program is improving the welfare of the community in the district. Bantaeng is to identify, socialize, and verify the potential beneficiaries and other training facilities. The supporting factors are the large number of agricultural and livestock commodities that can be processed into product businesses, the YESS program beneficiaries who have had previous businesses, and the government's support. The inhibiting factors are mutations of the YESS core organizers.